Rechargeable Battery Cell
A sulfur dioxide-based electrolyte with a chelate ligand structure addresses stability and safety issues in sodium ion cells, offering improved oxidative stability and extended service life, suitable for high-energy applications.
Patent Information
- Application Number
- JP2024536049
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-17
- Filing Date
- 2022-12-14
- Publication Date
- 2025-01-15
AI Technical Summary
Existing rechargeable sodium ion cells face issues with electrolyte stability, safety risks due to flammability, and limited operational life due to irreversible capacity loss and decomposition, particularly at high voltages and low temperatures, necessitating the development of a stable and safe electrolyte system.
A rechargeable battery cell using a sulfur dioxide-based system electrolyte with a specific conductive salt, characterized by a chelate ligand structure, which enhances oxidative stability and reduces decomposition, ensuring a wide potential window and low vapor pressure, thereby improving safety and longevity.
The proposed electrolyte system provides high oxidative stability, increased service life, and operational safety, with minimal decomposition and enhanced conductivity at low temperatures, making it suitable for high-energy applications.
Smart Images

Figure 2025500908000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a rechargeable battery cell comprising sodium as the active metal. [Background technology]
[0002] Rechargeable battery cells are of great importance in many technical fields. In many cases, they are used in applications where only small rechargeable battery cells with a relatively small current are needed, such as for example the operation of mobile phones. However, there is also a demand for larger rechargeable battery cells for high energy applications, and for the electric drive of vehicles, it is especially important to store large amounts of energy in the form of battery cells.
[0003] An important requirement for this type of rechargeable battery cell is a high energy density. This means that the rechargeable battery cell must contain as much electrical energy as possible per unit of weight and volume. Lithium has proven to be particularly advantageous as an active metal for this purpose. However, a drawback of lithium cells is the limited lithium resources on Earth. Therefore, many research groups in the field are trying to find an alternative to lithium as an active metal that on the one hand has the main advantages of lithium, but at the same time is easily available and cheap. Sodium is being investigated as an alternative to lithium. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] U.S. Patent Application No. 4,891,281 [Patent Document 2] European Patent Application Publication No. 2860799 [Patent Document 3] European Patent Application Publication No. 2860811 [Patent Document 4] European Patent Application Publication No. 3772129 [Non-patent literature]
[0005] [Non-Patent Document 1] I. Krossing, European Journal of Chemistry, 2001, 7, 490 [Non-Patent Document 2] P. J. Malinowski et al., Dalton Transactions, 2020, 49, 7766-7773 Summary of the Invention
[0006] The active metal of a rechargeable battery cell refers to a metal whose ions in the electrolyte migrate to the negative or positive electrode during charging or discharging of the cell, where they participate in an electrochemical process. The electrochemical process leads, directly or indirectly, to the release or absorption of electrons to or from an external circuit. As mentioned above, the active metal can be lithium or sodium. Rechargeable battery cells containing lithium or sodium as the active metal are referred to as lithium-ion or sodium-ion cells. Lithium-ion cells have been known for some time and are described in detail in the prior art. Sodium-ion cells, on the other hand, have only become a research focus since 2010 and are described in more detail below. Most research activities have been devoted to finding high-performance anodes (Hochleistungsanoden) to increase the energy density of sodium-ion cells, since the main material in lithium-ion cells, graphite, has a much lower storage capacity for sodium compared to lithium.
[0007] Like other rechargeable battery cells, sodium-ion cells have a housing in which at least one positive electrode with a conductor element, at least one negative electrode with a conductor element, and an electrolyte are arranged. Both the positive and negative electrodes of sodium-ion cells known from the prior art are formed as intercalation electrodes. The term "intercalation electrode" in the sense of the present invention is understood to mean an electrode with a crystalline structure, which is capable of storing or releasing ions of an active metal in the crystalline structure during operation of the sodium-ion cell. This means that electrode processes can take place not only on the surface of the electrode, but also within the crystalline structure.
[0008] The electrolyte is also an important functional element for all rechargeable battery cells. It usually comprises a solvent or a solvent mixture and at least one conductive salt. Solid electrolytes or ionic solutions, for example, do not contain a solvent and only contain a conductive salt. The electrolyte is in contact with the positive and negative electrodes of the battery cell. At least one ion (anion or cation) of the conductive salt is mobile in the electrolyte so that the charge transport between the electrodes, which is necessary for the functioning of the rechargeable battery cell, can be carried out by ionic conduction. The electrolyte is electrochemically decomposed oxidatively above a certain upper cell voltage of the rechargeable battery cell. This process often leads to the irreversible destruction of the electrolyte components and thus to the failure of the rechargeable battery cell. Reduction processes can also destroy the electrolyte below a certain lower cell voltage limit. To avoid the process, the positive and negative electrodes are selected so that the cell voltage is smaller or larger than the decomposition voltage of the electrolyte. The electrolyte thus determines the voltage window (in English: voltage window) within which the rechargeable battery cell can be operated reversibly, i.e. repeatedly charged and discharged.
[0009] Organic sodium-ion cells known from the prior art contain an electrolyte consisting of an organic solvent or solvent mixture and a conductive salt dissolved therein. The conductive salt is a sodium salt, such as, for example, sodium perchlorate (NaClO4) or sodium hexafluorophosphate (NaPF6). The organic solvent mixture may be, for example, propylene carbonate (PC). The solvent mixture may contain, for example, ethylene carbonate (EC), diethyl carbonate (DEC) or dimethyl carbonate (DMC). For example, the following mixtures are used: EC:DEC, EC:PC, or EC:DMC.
[0010] Due to the use of an organic solvent or solvent mixture, this type of sodium-ion cell is also called an organic sodium-ion cell.
[0011] A suitable negative electrode for an organic sodium-ion cell consists of a modified carbon, e.g. hard carbon. The capacity of hard carbon is 300 mAh / g and the cycling efficiency in the first cycle is 80%. A positive electrode for an organic sodium-ion cell consists of e.g. NaMeO x or polyanionic compounds such as phosphate (NaMePO4), pyrophosphate (Na2MeP2O7) and fluorophosphate (Na2Me(PO)4F), where "Me" represents each transition metal.
[0012] Since sodium is a very electronegative metal (-2.71 V vs. standard hydrogen electrode, SHE), a very high cell voltage is generated relative to the positive electrode. At the negative electrode, the reduction of the organic electrolyte takes place. The reductive decomposition is irreversible. No organic solvent is thermodynamically stable towards sodium or sodium stored on carbon. However, many solvents form a passivation film on the negative electrode surface. The film spatially separates the solvent from the electrode but allows the passage of sodium ions by having ionic conductivity. The passivation film, the so-called "Solid Electrolyte Interphase (SEI)", allows the fabrication of organic sodium-ion cells by providing stability to the system. During the formation of the SEI, sodium is integrated into the passivation film. This process is irreversible and is therefore considered a capacity loss. The irreversible capacity loss, also called the cover layer capacity, depends on the electrolyte formulation used and the electrode used. In organic sodium-ion cells, the electrolyte decomposition and the formation of a sodium ion-containing layer during the continued operation of the organic sodium-ion cell often take time, which causes capacity loss and therefore a short lifespan of the organic sodium-ion cell. Organic sodium-ion cells therefore have problems with their own stability and operational safety during long-term use. Safety risks also arise, in particular due to the flammability of the organic solvents or solvent mixtures. If the organic sodium-ion cell catches fire or even explodes, the organic solvents of the electrolyte form flammable materials. A further disadvantage of organic sodium-ion cells is the decomposition of the organic components of the SEI layer and the release of toxic gases associated with the decomposition. In addition, this causes the cell to heat up further. In order to avoid such safety risks, further measures must be taken. These include very precise control of the organic sodium-ion cell, in particular the charge and discharge process. However, additional measures are considered to be disadvantageous for possible commercialization.
[0013] In a development known from the prior art, an electrolyte based on sulfur dioxide (SO2) is used in rechargeable battery cells instead of an organic electrolyte. Rechargeable battery cells containing an SO2-based electrolyte have a particularly high ionic conductivity. The term "SO2-based electrolyte" is understood to mean an electrolyte which does not only contain SO2 in low concentrations as an additive, but in which the ionic mobility of the conductive salt contained in the electrolyte and which carries out the charge transport is ensured at least partially, mostly or completely by SO2. SO2 thus acts as a solvent for the conductive salt. The conductive salt can form liquid solvate complexes with gaseous SO2, in which the SO2 is bound and the vapor pressure is significantly reduced compared to pure SO2. An electrolyte with a lower vapor pressure is produced. This type of SO2-based electrolyte has the advantage of being non-flammable compared to the aforementioned organic electrolytes. It is thus possible to eliminate safety risks resulting from the flammability of the electrolyte.
[0014] Mainly LiAlCl4 * An SO2-based electrolyte with the composition xSO2 is used. However, sodium conductive salts have also been investigated. US Patent Application No. 4,891,281 (referred to as [V1]) shows work with lithium and sodium conductive salts, for example LiAlCl4 and NaAlCl4, among others, in SO2-based electrolytes. However, it is known from the literature that electrolytes with NaAlCl4 conductive salt have a worse conductivity than electrolytes with LiAlCl4 conductive salt. EP Patent Application No. 2,860,799 (referred to as [V2]) shows that NaAlCl4 * A rechargeable alkaline ion battery is disclosed that has an SO2-based electrolyte with a composition of xSO2. In one example, the combination of the electrolyte, a sodium metal anode, and a carbon-containing cathode that oxidizes or reduces SO2 as the active electrode material during operation of the battery cell is shown.
[0015] European Patent Application Publication No. 2860811 (referred to as [V3]) discloses NaAlCl4 *A battery cell is disclosed having an electrolyte with a composition of xSO2, a metal chloride-containing cathode, and an anode containing a sodium-containing inorganic material.
[0016] Alkaline conductive salts of tetrachloroaluminate (e.g. LiAlCl4 * xSO2 or NaAlCl4 * In addition to xSO2), EP 3772129 A1 (referred to as [V4]) discloses a new family of conductive salts for SO2-based electrolytes. The conductive salts consist of an anion with four substituted hydroxyl groups grouped around a central atom of boron or aluminum, and a cation consisting of the active metal of the cell. All examples show experiments with only lithium salts of this type.
[0017] The problem with SO2-based electrolytes is that many conductive salts, especially known in organic sodium-ion cells, are insoluble in SO2 and therefore it is not suitable to use conductive salts in rechargeable sodium-ion cells with SO2-based electrolytes.
[0018] The invention is thus based on the task of providing a rechargeable battery cell which, relative to the electrolytes known from the prior art, has the following properties: - Lithium-free, - Contains an SO2-based electrolyte that is a good ionic conductor and electronic insulator with good solubility of conductive salts, thus facilitating ion transport and minimizing self-discharge; - Contains an SO2-based electrolyte that is inert to other components in a rechargeable battery cell, such as the separator, electrode materials, and cell housing materials; - It has a wide potential window so that oxidative electrolyte decomposition does not occur at the positive electrode. - has a stable cover layer on the negative electrode, the cover layer capacity is low, and no further reductive electrolyte decomposition occurs in the negative electrode upon further operation; - Robust against electrical, mechanical, or thermal abuse; - Contains SO2-based electrolytes, which contain raw materials that are economically cheap and readily available, The negative conductor element can also be an aluminium conductor element.
[0019] Furthermore, rechargeable battery cells of this type are intended to have particularly good energy and performance data, high operational stability and life span, in particular a high number of usable charge / discharge cycles, without the electrolyte being decomposed during operation of the rechargeable battery cell.
[0020] The problem on which the invention is based has surprisingly been solved by a rechargeable battery cell having the features of claim 1. Claims 2 to 20 describe advantageous developments of the rechargeable battery cell according to the invention. Advantageous further developments of the rechargeable battery cell according to the invention can be seen from the description, the examples and the drawings.
[0021] The rechargeable battery cell according to the present invention comprises an active metal, at least one positive electrode, at least one negative electrode, a housing, and an electrolyte, the active metal being sodium. The electrolyte is based on SO2 and has the formula (I): [ka] In formula (I), the compound includes at least one first conductive salt having the substituent R 1 , R 2 and R 3 are independently halogen atoms, hydroxy groups, and the chemical group -OR 5 The substituent R is selected from the group formed by 4 is a hydroxy group and a chemical group -OR 5 and the substituent R is selected from the group formed by 5 is C1~C 10 Alkyl, C2-C 10 Alkenyl, C2-C 10 Alkynyl, C3-C 10 Cycloalkyl, C6-C 14 Aryl and C5-C 14The substituent R is selected from the group formed by heteroaryl, aliphatic, cyclic, aromatic, and heteroaromatic groups, which may be unsubstituted or substituted. 1 , R 2 , R 3 , and R 4 At least two of these are capable of forming chelating ligands coordinated together to Z, and are either aluminum or boron.
[0022] The term "substituent R" in the sense of the present invention 1 , R 2 , R 3 , and R 4 The term "chelating ligand formed together from at least two of the substituents R 1 , R 2 , R 3 , and R 4 It is understood that at least two of the substituents may be bridged to each other, and a bridge by two substituents leads to the formation of a bidentate chelating ligand. A chelating ligand can be, for example, of the formula -OR 5 It can be formed to be bidentate based on -O-. 5 To form -O-, the first substituent R 1 is preferably OR 5 Group, second substituent R 2 is preferably a hydroxy group, and the substituents are linked together by the formation of a chemical bond in their bridged state to form the aforementioned formula -OR 5 The chelating ligand may have, for example, the following structure: [ka]
[0023] The chelating ligand coordinates to the central atom Z to form a chelate complex. 5In the case of -O-, both oxygen atoms are coordinated to the central atom Z. Such chelate complexes can be prepared synthetically as described in Example 1 below. The term "chelate complex" refers to a complex compound in which a multidentate ligand (having one or more free electron pairs) occupies at least two coordination sites (bonding sites) of the central atom. A chelate ligand is a compound in which the substituent R 1 , R 2 , R 3 , and R 4 It may also be a polydentate ligand when three or four of them are cross-linked with each other. The SO2-based electrolyte used in the rechargeable battery cell according to the invention contains SO2 not only as an additive in low concentration, but also in a concentration in which the mobility of the ions of the first conductive salt contained in the electrolyte and responsible for the charge transport is at least partially, mostly or completely ensured by SO2. The first conductive salt dissolves in the electrolyte and has very good solubility therein. The conductive salt can form a liquid solvate complex with gaseous SO2, in which SO2 is bound. In this case, the vapor pressure of the liquid solvate complex is significantly reduced with respect to pure SO2, and an electrolyte with a lower vapor pressure is produced. However, it is also within the scope of the invention that, depending on the chemical structure of the first conductive salt according to formula (I), no reduction in vapor pressure can occur during the preparation of the electrolyte according to the invention. In the latter case, it is preferable to work at low temperature or under pressure during the preparation of the electrolyte according to the invention. It is also possible for the electrolyte to contain several conductive salts according to formula (I), whose chemical structures differ from one another. In the sense of the invention, "C1-C 10 The term "alkyl" comprises linear or branched saturated hydrocarbon groups having from 1 to 10 carbon atoms, including, in particular, methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, 2,2-dimethylpropyl, n-hexyl, isohexyl, 2-ethylhexyl, n-heptyl, isoheptyl, n-octyl, isooctyl, n-nonyl, n-decyl, and the like.
[0024] In the sense of the present invention, "C2-C 10The term "alkenyl" comprises unsaturated linear or branched hydrocarbon radicals having 2 to 10 carbon atoms, the hydrocarbon radical having at least one C-C double bond, including, in particular, ethenyl, 1-propenyl, 2-propenyl, 1-n-butenyl, 2-n-butenyl, isobutenyl, 1-pentenyl, 1-hexenyl, 1-heptenyl, 1-octenyl, 1-nonenyl, 1-decenyl, and the like.
[0025] In the sense of the present invention, "C2-C 10 The term "alkynyl" comprises unsaturated linear or branched hydrocarbon radicals having from 2 to 10 carbon atoms, the hydrocarbon radical having at least one C-C triple bond, including, in particular, ethynyl, 1-propynyl, 2-propynyl, 1-n-butynyl, 2-n-butynyl, isobutynyl, 1-pentynyl, 1-hexynyl, 1-heptynyl, 1-octynyl, 1-nonynyl, 1-decynyl, and the like.
[0026] In the sense of the present invention, "C3-C 10 The term "cycloalkyl" comprises cyclic saturated hydrocarbon groups having from 3 to 10 carbon atoms, including in particular cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclohexyl, cyclononyl and cyclodecanyl.
[0027] In the sense of the present invention, "C6-C 14 The term "aryl" comprises aromatic hydrocarbon groups having 6 to 14 cyclic carbon atoms. This includes, in particular, phenyl (CH), naphthyl (CH), ... 10 H7 group) and anthracyl (C 14 H9 group) is applicable.
[0028] In the sense of the present invention, "C5-C 14The term "heteroaryl" comprises aromatic hydrocarbon groups having 5 to 14 cyclic hydrocarbon atoms, at least one of which is substituted or replaced by a nitrogen, oxygen or sulfur atom. This applies in particular to pyrrolyl, furanyl, thiophenyl, pyridinyl, pyranyl, thiopyranyl, etc. All the aforementioned hydrocarbon groups are linked to the central atom according to formula (I) via the respective oxygen atom I.
[0029] In the context of the present invention, in the definitions of all the above terms, the aliphatic, cyclic, aromatic and heteroaromatic residues / groups may be unsubstituted or substituted, in which case the hydrogen atoms of the aliphatic, cyclic, aromatic and heteroaromatic residues / groups, respectively, are replaced by atoms such as fluorine or chlorine or by chemical groups such as CF3.
[0030] The rechargeable battery cell according to the invention has a first major advantage over lithium-ion cells known from the prior art, due to the use of cheap and readily available sodium as the active metal.
[0031] Moreover, the rechargeable battery cell according to the present invention having such an electrolyte has the advantage that no decomposition occurs at higher cell voltages, due to the higher oxidation stability of the first conductive salt according to formula (I) contained in the rechargeable battery cell, compared to rechargeable battery cells having an SO2-based electrolyte with a sodium conductive salt known from the prior art. The electrolyte has oxidation stability preferably up to an upper potential limit of at least 3.6 volts, more preferably up to an upper potential limit of at least 3.8 volts, more preferably up to an upper potential limit of at least 4.0 volts, more preferably up to an upper potential limit of at least 4.2 volts, more preferably up to an upper potential limit of at least 4.4 volts, and particularly preferably up to an upper potential limit of at least 4.6 volts. Thus, when using a rechargeable battery cell according to the present invention comprising such an electrolyte, there is no or very little electrolyte decomposition occurring within the working potential, i.e. in the range between the end-of-charge voltage and the end-of-discharge voltage of both electrodes of the rechargeable battery cell.
[0032] The life span of a rechargeable battery cell containing an electrolyte is significantly increased compared to rechargeable battery cells containing electrolytes known from the prior art.
[0033] Furthermore, rechargeable battery cells containing such electrolytes have low temperature stability: the conductivity of the electrolyte at low temperatures is sufficient to operate the battery cell.
[0034] The advantages of the rechargeable battery cell according to the invention comprising the electrolyte outweigh the disadvantages caused by the significantly larger anion size of the first conductive salt according to formula (I) compared to the sodium conductive salts known from the prior art, which leads to a lower conductivity of the first conductive salt according to formula (I) compared to that of NaAlCl4.
[0035] negative electrode Advantageous developments of the rechargeable battery cell according to the invention with respect to the negative electrode are described below: In an advantageous development of the rechargeable battery cell, the active material of the negative electrode consists of metallic sodium and / or at least one sodium storage material selected from the group formed by insertion materials, adsorption materials, alloy-forming materials and conversion materials.
[0036] According to an advantageous development of the rechargeable battery cell according to the invention, the active material of the negative electrode is metallic sodium. This means that sodium is also the active metal of the rechargeable battery cell. The active metal is deposited on the conductor element of the negative electrode during charging of the rechargeable battery cell. This means that the negative electrode, in addition to metallic sodium, also comprises a conductor element as active material. The conductor element is used to enable the necessary electronically conductive connection of the active material of the negative electrode. For this purpose, the conductor element is in contact with the active material participating in the electrode reaction of the negative electrode. During discharge of the rechargeable battery cell, metallic sodium is converted into sodium ions, which migrate from the negative electrode to the positive electrode.
[0037] In another advantageous development of the rechargeable battery cell according to the invention with metallic sodium as the active material of the negative electrode, the conductor element with electronic conductivity of the negative electrode already comprises metallic sodium before the first charging of the rechargeable battery cell, the metallic sodium being applied to the conductor element before the assembly of the battery cell and incorporated together with the conductor element into the battery cell, or being deposited on the conductor element of the negative electrode by a preceding initialization charging process before the operation of the battery cell, i.e. before the first charging and discharging. In another advantageous development of the rechargeable battery cell according to the invention with metallic sodium as the active material of the negative electrode, the conductor element of the negative electrode is at least partially formed from a sodium storage material. In such a development, during charging of the rechargeable battery cell, first a part of the sodium obtained as a result of the electrode reaction is stored from the sodium storage material in the conductor element with electronic conductivity. Then, during further charging of the battery cell, metallic sodium is deposited from the conductor element with electronic conductivity. During discharge, the metallic sodium dissolves completely or partially and reaches in the form of ions into the host matrix of the active material of the positive electrode.
[0038] According to another advantageous development of the rechargeable battery cell according to the invention, the active material of the negative electrode consists of at least one sodium storage material selected from the group formed by insertion materials, adsorption materials, alloy-forming materials and conversion materials.
[0039] The term "intercalation material" in the sense of the present invention is understood to be a material in which ions of an active metal can be stored during charging of a rechargeable battery cell and from which ions of an active metal can be released during discharging of the rechargeable battery cell, which means that electrode processes can take place not only on the surface of the negative electrode but also inside the negative electrode.
[0040] The term "sorbent material" in the context of the present invention is understood to be a material, in contrast to an intercalation material, that has a structure in which ions of the active metal can be deposited and released during operation of the sodium-ion cell, and on whose surface the ions accumulate. In many materials intercalation and adsorption are carried out simultaneously.
[0041] The term "alloying material" in the context of the present invention is generally understood to be a material that is a metal, metal alloy, and oxide of a metal and metal alloy that forms an alloy with an active metal, such as sodium, and the alloy formation occurs in or at the negative electrode and is essentially reversible. In contrast to insertion materials, the active metal in the alloy is not accumulated in an existing structure. Instead, the accumulation of the active metal is carried out by a phase transformation process, which may result in a binary sodium-containing end product, for example, when sodium is used as the active metal. During alloy formation, the active material may expand.
[0042] The term "conversion material" in the sense of the present invention is understood to be a material that undergoes a chemical conversion or transformation during the electrode process, which leads to the reversible formation of a chemical compound between an active metal and an active material.
[0043] In another advantageous development of the rechargeable battery cell according to the invention, the sodium storage material can be an insertion material, preferably containing carbon. The term "insertion material made of carbon" in the context of the invention is understood to mean a material made of elemental carbon, which corresponds to the above-defined "insertion material". In another advantageous development of the rechargeable battery cell according to the invention, the carbon-containing insertion material is selected from the group formed by hard carbon (English: hard carbon), soft carbon (English: soft carbon), graphene or heteroatom-doped carbon. Hard carbon (hard carbon) can be synthesized by carbonization of various precursors, such as, for example, biomass, lignin, cellulose and many types of polymers. Carbon-containing materials of fossil fuel origin (coke, pitch, etc.) are generally considered to be soft (graphitizable) and are classified in the soft carbon group (soft carbon). Heteroatom-doped carbon is carbon that, in addition to carbon atoms, contains additional atoms in its structure or on its surface, such as, for example, nitrogen, oxygen, sulfur, phosphorus.
[0044] In another advantageous development of the rechargeable battery cell according to the invention, the carbon-containing intercalation material is hard carbon (English: hard carbon).
[0045] In another advantageous development of the rechargeable battery cell according to the invention, the carbon-containing intercalation material is soft carbon (English: soft carbon).
[0046] In another advantageous development of the rechargeable battery cell according to the invention, the carbon-containing intercalation material is graphene.
[0047] In another advantageous development of the rechargeable battery cell according to the invention, the carbon-containing intercalation material is heteroatom-doped carbon.
[0048] In a further advantageous development of the rechargeable battery cell according to the invention, sodium ions can also be adsorbed on the surface.
[0049] In another advantageous development of the rechargeable battery cell according to the invention, the sodium storage material of the negative electrode consists of at least one carbon-free intercalation material, such as, for example, sodium titanate, in particular Na2Ti3O7, or NaTi2(PO4)3. The term "carbon-free intercalation material" in the sense of the present invention is understood to mean a material that consists of elements other than carbon, which corresponds to the above-defined "intercalation material".
[0050] In another advantageous development of the rechargeable battery cell according to the invention, the sodium storage material of the negative electrode consists of at least one sodium-alloying material. By the term "sodium-alloying material" in the sense of the present invention is understood an alloying material as defined above which forms an alloy with sodium.
[0051] As alloying materials, for example, sodium storage metals and metal alloys (e.g., Sn, Sb) can be used. Alternatively, sulfides or oxides of sodium storage metals and metal alloys (e.g., SnS x , SbS x, or oxide glasses of Sn, Sb, etc.) can be alloy-forming materials. In another advantageous development of the rechargeable battery cell according to the invention, the anode active material which forms an alloy with sodium already contains sodium before use in the battery cell. This measure reduces the capacity loss due to the formation of a cover layer, for example in the first cycle.
[0052] In another advantageous development of the rechargeable battery cell according to the invention, the sodium storage material of the negative electrode consists of at least one sodium storage material, which is a conversion material as defined above. The conversion material is selected from the group consisting of sulfides, oxides, selenides and fluorides of the metals Ti, V, Cr, Mn, Fe, Co, Ni, Cu and Zn, in particular iron sulfide (FeS x ), iron selenide (FeSe x ), iron fluoride (FeF x ), iron oxide (FeO x ), cobalt oxide (CoO x ), Nickel oxide (NiO x ), and copper oxide (CuO x )
[0053] In another advantageous development of the rechargeable battery cell according to the invention, the negative electrode consists of a combination of the aforementioned sodium storage materials, for example tin (Sb) and / or tin sulfide (SnS x It is possible to use a combination of carbide and hard carbon.
[0054] In another advantageous development of the rechargeable battery cell according to the invention, the negative electrode is porous, with a porosity of preferably at most 50%, more preferably at most 45%, more preferably at most 40%, more preferably at most 35%, more preferably at most 30%, more preferably at most 20% and particularly preferably at most 10%. The porosity refers to the void volume relative to the total volume of the negative electrode, the void volume being formed by so-called holes or voids. The porosity leads to an increase in the internal surface of the negative electrode. Furthermore, the porosity reduces the density of the negative electrode, thereby also reducing its weight. Preferably, the individual pores of the negative electrode can be completely filled with electrolyte during operation.
[0055] In another advantageous development of the rechargeable battery cell according to the invention, the negative electrode has a conductor element. This means that the negative electrode comprises a conductor element in addition to the active material or intercalation material. The conductor element is used to enable the necessary electronically conductive connection of the active material of the negative electrode. For this purpose, the conductor element is in contact with the active material participating in the electrode reaction of the negative electrode. The conductor element can be formed planar in the form of a thin metal sheet or thin metal foil. The thin metal foil preferably has a perforated or mesh-like structure. The planar conductor element can also consist of a metal-coated plastic foil. The metal coating has a thickness in the range of 0.1 μm to 20 μm. The active material of the negative electrode is preferably applied to the surface of the thin metal sheet, thin metal foil or metal-coated plastic foil. The active material can be applied to the front and / or rear side of the planar conductor element. Planar conductor elements of this kind have a thickness in the range of 5 μm to 50 μm. A thickness of the planar conductor element in the range of 10 μm to 30 μm is preferred. When planar conductor elements are used, the total thickness of the negative electrode can be at least 20 μm, preferably at least 40 μm, and particularly preferably at least 60 μm. The maximum thickness is at most 200 μm, preferably at most 150 μm, and particularly preferably at most 100 μm. The area-specific capacity of the negative electrode relative to the coating on one side is preferably at least 0.5 mAh / cm when planar conductor elements are used.2 and furthermore the following values in this order are preferred: 1 mAh / cm 2 , 3mAh / cm 2 , 5mAh / cm 2 , 10mAh / cm 2 , 15mAh / cm 2 , 20mAh / cm 2 .
[0056] There is also the possibility of forming the conductor elements three-dimensionally in the form of a porous metal structure, in particular in the form of a metal foam. The term "three-dimensional porous metal structure" refers to any metallic structure that extends not only over the length and width of a planar electrode, such as a thin metal sheet or foil, but also over its thickness dimension. The three-dimensional porous metal structure is porous, so that the active material of the negative electrode can be incorporated into the pores of the metal structure. The amount of active material incorporated or applied refers to the loading of the negative electrode. When the conductor elements are formed three-dimensionally in the form of a porous metal structure, in particular in the form of a metal foam, the negative electrode preferably has a thickness of at least 0.2 mm, preferably at least 0.3 mm, more preferably at least 0.4 mm, more preferably at least 0.5 mm, and particularly preferably at least 0.6 mm. In this case, the thickness of the electrode is significantly greater compared to the negative electrodes used in organic sodium-ion cells. In another advantageous embodiment, the area-specific capacity of the negative electrode, in particular when using three-dimensional conductor elements in the form of a metal foam, is preferably at least 2.5 mAh / cm 2 and the following values are more preferred in this order: 2 , 15mAh / cm 2 , 25mAh / cm 2 , 35mAh / cm 2 , 45mAh / cm 2 , 55mAh / cm 2 , 65mAh / cm 2 , 75mAh / cm 2 If the conductor element is formed in the form of a three-dimensionally porous metal structure, in particular in the form of a metal foam, the amount of active material of the negative electrode, i.e. the filling of the electrode with respect to its surface, must be at least 10 mg / cm 2, preferably at least 20 mg / cm 2 , and more preferably at least 40 mg / cm 2 , and more preferably at least 60 mg / cm 2 , and more preferably at least 80 mg / cm 2 and particularly preferably at least 100 mg / cm 2 The negative electrode loading has a positive effect on the charging and discharging processes of a rechargeable battery cell.
[0057] The conductor element of the negative electrode can be made of, for example, nickel or copper. The potential of the active metal sodium is slightly higher than that of the active metal lithium used, for example, in lithium-ion batteries. This allows the use of aluminum as the conductor element in sodium cells, in contrast to lithium, without sodium forming an alloy with aluminum.
[0058] In another advantageous development of the battery cell according to the invention, the negative electrode has at least one binder. The binder is preferably a fluorinated binder, in particular polyvinylidene fluoride and / or a terpolymer formed by tetrafluoroethylene, hexafluoropropylene and vinylidene fluoride. However, it may also be a binder consisting of a polymer consisting of monomeric structural units of conjugated carboxylic acids or of alkali metal, alkaline earth metal or ammonium salts of conjugated carboxylic acids or a combination thereof. It is further possible for the binder to consist of a polymer based on monomeric styrene and butadiene structural units. It may also be a binder consisting of a binder from the carboxymethylcellulose group. The binder is preferably present in the negative electrode in a concentration of at most 20% by weight, more preferably at most 15% by weight, more preferably at most 10% by weight, more preferably at most 7% by weight, more preferably at most 5% by weight and particularly preferably at most 2% by weight, based on the total weight of the negative electrode.
[0059] In another advantageous development of the battery cell according to the invention, the negative electrode comprises at least one conductive additive. The conductive additive preferably has low weight, high chemical resistance and high specific surface area. Examples of conductive additives are particulate carbon (carbon black, super P, acetylene black), fibrous carbon (carbon nanotubes CNT, carbon (nano)fibers), finely divided graphite and graphene (nanosheets).
[0060] electrolyte In the following, advantageous developments of the rechargeable battery cell according to the invention with respect to an SO2-based electrolyte are described.
[0061] In a first advantageous development of the rechargeable battery cell according to the invention, the substituent R 1 , R 2 , R 3 , and R 4 are each independently a chemical group -OR 5 R 5 is C1~C 10 Alkyl, C2-C 10 Alkenyl, C2-C 10 Alkynyl, C3-C 10 Cycloalkyl, C6-C 14 Aryl and C5-C 14 Heteroaryl, aliphatic, cyclic, aromatic, and heteroaromatic groups may be unsubstituted or substituted.
[0062] In a further advantageous development of the rechargeable battery cell according to the invention, R 5 is selected from the group formed by: - C1-C6 alkyl, preferably C2-C4 alkyl, particularly preferably 2-propyl, methyl and ethyl, - C2-C6 alkenyl, preferably C2-C4 alkenyl, particularly preferably ethenyl and propenyl, - C2-C6 alkynyl, preferably C2-C4 alkynyl, - C3-C6 cycloalkyl, - Phenyl, and - C5-C7 heteroaryl, - the aliphatic, cyclic, aromatic and heteroaromatic groups may be unsubstituted or substituted.
[0063] The terms "C1-C6 alkyl", "C2-C6 alkenyl", "C2-C6 alkynyl", "C3-C6 cycloalkyl", and "heteroaryl" are as defined above.
[0064] In another advantageous development of the rechargeable battery cell according to the invention, the substituent R 5 at least one individual atom or one group of atoms is replaced by a halogen atom, in particular a fluorine atom, or by a chemical group selected from the group formed by C1-C4 alkyl, C2-C4 alkenyl, C2-C4 alkynyl, phenyl, benzyl, and fully to partially halogenated, in particular fully to partially fluorinated, C1-C4 alkyl, C2-C4 alkenyl, C2-C4 alkynyl, phenyl, and benzyl. The chemical groups C1-C4 alkyl, C2-C4 alkenyl, C2-C4 alkynyl, phenyl, and benzyl have similar properties or chemical structures as the aforementioned hydrocarbon groups.
[0065] Substituent R 5 At least one of the atomic groups is preferably a CF3 group or an OSO2CF3 group, which makes it possible to obtain a particularly high solubility of the first conductive salt in the SO2-based electrolyte.
[0066] In a further advantageous development of the rechargeable battery cell according to the invention, the substituent R 1 , R 2 , R 3 , and R 4is a hydroxy group (-OH). The hydrogen atom (H) of the hydroxy group may be replaced by a chemical group formed from C1-C4 alkyl, C2-C4 alkenyl, C2-C4 alkynyl, phenyl, benzyl, and fully to partially halogenated, in particular fully to partially fluorinated, C1-C4 alkyl, C2-C4 alkenyl, C2-C4 alkynyl, phenyl, and benzyl. The chemical groups C1-C4 alkyl, C2-C4 alkenyl, C2-C4 alkynyl, phenyl, and benzyl have similar properties or chemical structures as the aforementioned hydrocarbon groups and fall under the aforementioned definitions.
[0067] In another advantageous development of the rechargeable battery cell according to the invention, the first conductive salt is selected from the group formed by: [ka]
[0068] In order to adapt the conductivity and / or further properties of the electrolyte to the desired values, in another preferred embodiment of the rechargeable battery cell according to the invention, the electrolyte comprises at least one second conductivity salt different from the first conductivity salt according to formula (I), which means that in addition to the first conductivity salt, the electrolyte may comprise one or more second conductivity salts which differ from the first conductivity salt not only in their chemical composition but also in their chemical structure.
[0069] In another preferred embodiment of the rechargeable battery cell according to the invention, the second conductive salt is an alkali metal compound, in particular a sodium compound. The alkali metal or sodium compound is selected from the group formed by aluminates, halides, oxalates, borates, phosphates, arsenates and gallates. The second conductive salt is preferably a sodium tetrahaloaluminate, in particular NaAlCl4.
[0070] In yet another preferred embodiment of the rechargeable battery cell according to the invention, the electrolyte comprises at least one additive, which may be selected from the group consisting of vinylene carbonate and its derivatives, vinyl ethylene carbonate and its derivatives, methyl ethylene carbonate and its derivatives, sodium (bisoxalato)borate, sodium difluoro(oxalato)borate, sodium tetrafluoro(oxalato)phosphate, sodium oxalate, 2-vinylpyridine, 4-vinylpyridine, cyclic exomethylene carbonate, sultones, cyclic and acyclic sulfonates, acyclic sulfites, cyclic and acyclic sulfinic acid esters, organic esters of inorganic acids, acyclic and cyclic alkanes (acyclic and and cyclic alkanes having a boiling point of at least 36° C. at 1 bar), aromatic compounds, halogenated cyclic and acyclic sulfonylimides, halogenated cyclic and acyclic phosphates, halogenated cyclic and acyclic phosphines, halogenated cyclic and acyclic phosphites, halogenated cyclic and acyclic phosphazenes, halogenated cyclic and acyclic silylamines, halogenated cyclic and acyclic halogenated esters, halogenated cyclic and acyclic amides, halogenated cyclic and acyclic anhydrides and halogenated organic heterocycles.
[0071] In another preferred embodiment of the rechargeable battery cell, the electrolyte has the following composition by weight of the total electrolyte composition: (i) 5 to 99.4% by weight of sulfur dioxide; (ii) 0.6 to 95 weight percent of a first conductive salt; (iii) 0 to 25 wt. % of a second conductive salt, and (iv) 0 to 10 wt. % of an additive.
[0072] As mentioned above, the electrolyte can contain not only one first conductive salt according to formula (I) and one second conductive salt, but also a plurality of first conductive salts and a plurality of second conductive salts, respectively, according to formula (I). In the latter case, the above-mentioned ratio includes a plurality of first conductive salts and a plurality of second conductive salts. The concentration of the substance amount of the first conductive salt is in the range of 0.01 mol / l to 10 mol / l, preferably 0.05 mol / l to 10 mol / l, preferably 0.1 mol / l to 6 mol / l, and particularly preferably 0.2 mol / l to 3.5 mol / l, based on the total volume of the electrolyte.
[0073] In another preferred embodiment of the rechargeable battery cell according to the invention, the electrolyte comprises at least 0.1 mol SO2 per mole of conductive salt, preferably at least 1 mol SO2, more preferably at least 5 mol SO2, more preferably at least 10 mol SO2 and particularly preferably at least 20 mol SO2. The electrolyte can also comprise a very high molar ratio of SO2, with a preferred upper limit of 2600 mol SO2 per mole of conductive salt, with upper limits of 1500, 1000, 500 and 100 mol SO2 per mole of conductive salt being preferred in that order. The term "per mole of conductive salt" refers to all conductive salts contained in the electrolyte. SO2-based electrolytes with this type of concentration ratio between SO2 and conductive salt have the advantage that the electrolyte is capable of dissolving a larger amount of conductive salt compared to electrolytes known from the prior art, for example based on organic solvent mixtures. Surprisingly, within the scope of the present invention, it has been found that electrolytes with a relatively small concentration of conductive salt are advantageous, in particular with regard to the stability of rechargeable battery cells over a large number of charge-discharge cycles, despite the associated increase in vapor pressure. The SO2 concentration in the electrolyte affects the conductivity of the electrolyte. Thus, by selecting the SO2 concentration, the conductivity of the electrolyte can be adapted to the intended use of the rechargeable battery cell operated by the electrolyte. The total weight of the SO2 and the first conductive salt can be more than 50 weight percent (wt%) of the weight of the electrolyte, preferably more than 60 wt%, more preferably more than 70 wt%, more preferably more than 80 wt%, more preferably more than 85 wt%, more preferably more than 90 wt%, more preferably more than 95 wt%, or even more preferably more than 99 wt%.
[0074] The electrolyte may contain at least 5% SO2 by weight, with more preferred values being 20% SO2, 40% SO2, and 60% SO2 by weight, based on the total amount of electrolyte contained in the rechargeable battery cell. The electrolyte may contain up to 95% SO2 by weight, with maximum values of 80% SO2 and 90% SO2 by weight being preferred in that order.
[0075] It is also within the scope of the present invention that the proportion of at least one organic solvent in the electrolyte is low or absent. Preferably, the proportion of organic solvent in the electrolyte, for example present in the form of a mixture of one or more solvents, may be at most 50% by weight of the electrolyte. Particularly preferred are smaller proportions, such as at most 40%, at most 30%, at most 20%, at most 15%, at most 10%, at most 5% or at most 1% by weight relative to the weight of the electrolyte. It is further preferred that the electrolyte is free of organic solvents. With a low or no organic solvent proportion, the electrolyte has little or no flammability. This improves the operational safety of rechargeable battery cells operated with this type of SO2-based electrolyte.
[0076] In another preferred embodiment of the rechargeable battery cell, the electrolyte has the following composition by weight of the total electrolyte composition: (i) 5 to 99.4% by weight of sulfur dioxide; (ii) 0.6 to 95 weight percent of a first conductive salt; (iii) 0 to 25 wt. % of a second conductive salt; (iv) 0 to 10 wt. % of an additive, and (v) 0 to 50% by weight of an organic solvent.
[0077] positive electrode In the following, advantageous developments of the rechargeable battery cell according to the invention with respect to the positive electrode are explained: In a first advantageous development of the rechargeable battery cell according to the invention, the positive electrode is preferably chargeable to an upper potential limit of at least 3.6 volts, preferably to an upper potential limit of at least 3.8 volts, further preferably to an upper potential limit of at least 4.0 volts, further preferably to an upper potential limit of at least 4.2 volts, further preferably to an upper potential limit of at least 4.4 volts and particularly preferably to an upper potential limit of at least 4.6 volts.
[0078] In another advantageous development of the rechargeable battery cell according to the invention, the positive electrode comprises at least one active material capable of storing active metallic sodium ions and releasing and reacquiring active metallic sodium ions during operation of the battery cell.
[0079] In another advantageous development of the rechargeable battery cell according to the invention, the positive electrode comprises at least one intercalation compound. The term "intercalation compound" in the context of the present invention is to be understood as a subcategory of the aforementioned intercalation materials. The intercalation compound serves as a host matrix with interconnected voids. During the discharge process of the rechargeable battery cell, ions of the active metal can diffuse into the voids and accumulate there. Little or no structural changes in the host matrix occur during the accumulation of ions of the active metal.
[0080] In another advantageous development of the rechargeable battery cell according to the invention, the positive electrode comprises at least one transformation compound as active material. The term "transformation compound" in the sense of the present invention is to be understood as a material which forms another material during electrochemical activity, i.e. chemical bonds are broken and reformed during charging and discharging of the battery cell. Upon acceptance and release of ions of the active metal, structural changes occur in the matrix of the transformation compound.
[0081] In another advantageous development of the rechargeable battery cell according to the invention, the active material is Na x M' y M” z O a The composition is M' is at least one metal selected from the group formed by the elements Ti, V, Cr, Mn, Fe, Co, Ni, Cu and Zn, M″ is at least one element selected from the group formed by the elements of groups 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 and 16 of the Periodic Table of the Elements, - x and y are each independently greater than 0; - z is a number equal to or greater than 0, and - a is a number greater than 0.
[0082] Composition Na x M' y M” z O a The indices y and z in the formula represent the sum of the metal and element represented by M' or M'', respectively. For example, M' is two metals, M' 1 and M' 2 In the case where the compound comprises a metal M', the index y is y=y1+y2, and y1 and y2 are each independently selected from the group consisting of a metal M' 1 and M' 2 The indices x, y, z and a must be selected so that the charge in the composition is neutral. An example of a compound where M' contains two metals is M' 1 =Ni,M' 2 = Mn and M" = Co, x Ni y1 Mn y2 Co z An example of a compound where z=0, i.e., there is no other metal or element M, is sodium cobaltate Na x Co y O a It is.
[0083] For example, M" is two elements, on the one hand, metal M" 1 On the other hand, M 2 When the compound contains phosphorus as the metal M, the index z is z=z1+z2, and z1 and z2 are each independently selected from the group consisting of the metal M" 1 Torin (M“ 2 The indices x, y, z and a must be selected so that the charge in the composition is neutral. M" is a metal M"1, M" 2 Examples of compounds containing phosphorus as a substituent include M'=Fe, M" 1 =Mn, M“ 2 = P and z2 = 1. x Fe y Mn z1 P z2O4. In other compositions, M" is two nonmetallic elements, e.g. M" 1 Fluorine as M 2 Examples of such compounds include M'=Fe, M" 1 =F and M“ 2 = Sodium iron fluorosulfate Na x Fe y F z1 S z2 He is O4.
[0084] In another advantageous development of the rechargeable battery cell according to the invention, Na x M' y M” z O a The compound has a layered oxide structure. M' or M" is a compound having two or more metals M' 1 , M' 2 , M' 3 Or M“ 1 , M“ 2 , M“ 3 An example of such a compound is NaNi 0.5 Mn 0.2 Ti 0.3 O2, Na 0.90 Cu 0.22 Fe 0.30 Mn 0.48 O2, Na 2 / 3 Ni 2 / 3 Te 1 / 3 O2, Na 2 / 3 Fe 1 / 2 Mn 1 / 2 O2, Na x MnO2, NaFe 1 / 2 Mn 1 / 2 O2, Na(Fe 1 / 3 Mn 1 / 3 Ni 1 / 3 )O2 and Na[Ni 0.4 Fe 0.2 Mn 0.2 Ti 0.2 ]O2. Preferred are compounds in which M' consists of the metals nickel and manganese and M" is cobalt, so that the compound has the formula Na x Ni y1 Mn y2 Co zO a and y1 and y2 are independently a number greater than 0. In this case, the formula Na x [Ni y1 Mn y2 Co z ]O2(NMC), i.e., sodium with a layered oxide structure. D Kuckel Ma Ngan Ko An example of an active material made of sodium nickel manganese cobalt oxide is Na[Ni 1 / 3 Mn 1 / 3 Co 1 / 3 ]O2 and Na 0.6 [Ni 0.25 Mn 0.5 Co 0.25 ]O2.
[0085] In another advantageous development of the rechargeable battery cell according to the invention, the composition is of the formula Na x M' y M” z O4. Such compounds have a spinel structure. For example, M' can be cobalt and M" can be manganese. In this case, the active material is sodium cobalt manganese oxide (NaCoMnO4).
[0086] In another advantageous development, the compound has the composition Na x M' y M” 1 z1 M” 2 z2 O a M” 1 and M.” 2 are at least one element selected from the group formed by the elements of groups 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 and 16 of the Periodic Table of the Elements, and M" 2 O a The polyanion structural unit may be, for example, of the composition (M 2 O4) n- , (M” 2 m O 3m+1) n- , or (M” 2 O3) n- where m and n are independently a number greater than 0. An example of such an anion is (SO4) 2- , (PO4) 3- , (SiO4) 2- , (AsO4) 3- , (MoO4) 2- , (WO4) 2- , (P2O7) 4- , (CO3) 2- , and (BO3) 3- It is.
[0087] M” 2 is the element phosphorus, the composition Na x M' y M” z1 M” z2 O a are the so-called sodium metal phosphates. Examples of such compounds are Na3V2(PO4)3, NaVPO4F, Na2CoP2O7, Na4Ni3(PO4)2P2O7, Na2MnPO4F, and Na2MnP2O7. 2 If is elemental sulfur, then Na x M' y M” z1 M” z2 O a The compounds with the composition are so-called sodium metal sulfates. Examples of this compound are NaFeSO4F and NaFe2(PO4)(SO4)2. The second compound is a compound with two polyanion structural units. M” 2 is the element silicon, the composition Na x M' y M” z1 M” z2 O a Compounds having the formula: are so-called sodium metal silicates. An example of this compound is Na2FeSiO4.
[0088] In another advantageous development of the rechargeable battery cell according to the invention, the active material has the composition Na x M' y [Fe(CN)6]a M' is at least one metal selected from the group formed by the elements Ti, V, Cr, Mn, Fe, Co, Ni, Cu and Zn. M' is at least one metal selected from the group formed by the elements Ti, V, Cr, Mn, Fe, Co, Ni, Cu and Zn. 1 , M' 2 , M' 3 etc. In this case, the index y is y=y1+y2, where y1 and y2 are the metals M' 1 and M' 2 n is a number equal to or greater than 0, and x, all the indices y (y, y1, y2, etc.) and a are numbers greater than 0, independently of one another. Compounds of this type are the hexacyanoferrates known in English as "Prussian blue" or "Prussian white". Examples of such compounds are Na2NiFe(CN)6, FeFe(CN)6 4H2O, Na 0.61 FeFe(CN)6, Na 1.89 Mn[Fe(CN)6] 0.97 and NaNi 0.3 Mn 0.7 The compound is Fe(CN)6.
[0089] In another advantageous development of the rechargeable battery cell according to the invention, the positive electrode comprises at least one active material which is a transformation compound. The transformation compound undergoes a solid-state redox reaction when it receives an active metal, for example sodium, during which the crystal structure of the material changes. This occurs under the breaking and reformation of chemical bonds. The fully reversible reaction of the transformation compound can be, for example, the following: Type A: MX z +yNa ⇔ M+zNa (y / z) X Type B: X+yNa ⇔ Na y X
[0090] The transformation compounds are sulfides, oxides, selenides, and fluorides of the metals Ti, V, Cr, Mn, Fe, Co, Ni, Cu, and Zn, especially iron sulfide (FeS x ), iron selenide (FeSe x ), iron fluoride (FeF x), iron oxide (FeO x ), cobalt oxide (CoO x ), Nickel oxide (NiO x ) and copper oxide (CuO x )
[0091] In another advantageous development of the rechargeable battery cell according to the invention, the positive electrode comprises at least one metal compound selected from the group formed by metal oxides, metal halides and metal phosphates, the metal of which is preferably a transition metal of atomic numbers 22 to 28 of the periodic table of the elements, in particular cobalt, nickel, manganese or iron.
[0092] In another advantageous development of the rechargeable battery cell according to the invention, the positive electrode comprises at least one metal compound having the chemical structure of a layered oxide, a spinel, a polyanionic compound or a modification compound.
[0093] It is within the scope of the present invention for the positive electrode to comprise at least one of the aforementioned compounds or combinations of compounds as an active material. By combination of compounds, it is meant a positive electrode that comprises at least two of the aforementioned materials.
[0094] In another advantageous development of the battery cell according to the invention, the positive electrode has a conductor element. This means that the positive electrode comprises a conductor element in addition to the active material. The conductor element is used to enable the necessary electronically conductive connection of the active material of the positive electrode. For this purpose, the conductor element is in contact with the active material participating in the electrode reaction of the positive electrode.
[0095] The conductor element may be formed planar in the form of a thin metal sheet or a thin metal foil. The thin metal foil preferably has a perforated or mesh structure. It is also possible for the planar conductor element to be formed by a metal-coated plastic foil. The metal coating has a thickness in the range of 0.1 μm to 20 μm. The active material of the positive electrode is preferably applied to the surface of the thin metal sheet, thin metal foil or metal-coated plastic foil. The active material may be applied to the front and / or rear surface of the planar conductor element. Planar conductor elements of this type have a thickness in the range of 5 μm to 50 μm. A thickness of the planar conductor element in the range of 10 μm to 30 μm is preferred. When planar conductor elements are used, the total thickness of the positive electrode may be at least 20 μm, preferably at least 40 μm and particularly preferably at least 60 μm. The maximum thickness is preferably at most 200 μm, preferably at most 150 μm and particularly preferably at most 100 μm. The area specific capacity of the positive electrode relative to the coating on one side is preferably at least 0.5 mAh / cm when using a planar conductor element. 2 and furthermore the following values in this order are preferred: 1 mAh / cm 2 , 3mAh / cm 2 , 5mAh / cm 2 , 10mAh / cm 2 , 15mAh / cm 2 , 20mAh / cm 2 .
[0096] It is also possible to form the conductor elements of the positive electrode in the form of a three-dimensional porous metal structure, in particular in the form of a metal foam. The three-dimensional porous metal structure is porous so that the active material of the positive electrode can be incorporated into the pores of the metal structure. The amount of incorporated or applied active material refers to the loading of the positive electrode. When the conductor elements are formed in the form of a three-dimensional porous metal structure, in particular in the form of a metal foam, the positive electrode preferably has a thickness of at least 0.2 mm, preferably at least 0.3 mm, more preferably at least 0.4 mm, more preferably at least 0.5 mm, and particularly preferably at least 0.6 mm. In another advantageous embodiment, the area-specific capacity of the positive electrode, in particular when using three-dimensional conductor elements in the form of a metal foam, is preferably at least 2.5 mAh / cm. 2 and the following values are more preferred in this order: 2 , 15mAh / cm 2 , 25mAh / cm 2 , 35mAh / cm 2 , 45mAh / cm 2 , 55mAh / cm 2 , 65mAh / cm 2 , 75mAh / cm 2 If the conductor element is formed in the form of a three-dimensionally porous metal structure, in particular in the form of a metal foam, the amount of active material of the positive electrode, i.e. the filling of the electrode with respect to its surface, is at least 10 mg / cm 2 , preferably at least 20 mg / cm 2 , and more preferably at least 40 mg / cm 2 , and more preferably at least 60 mg / cm 2 , and more preferably at least 80 mg / cm 2 and particularly preferably at least 100 mg / cm 2 The loading of the positive electrode has a positive effect on the charging process as well as the discharging process of the rechargeable battery cell.
[0097] In another advantageous development of the battery cell according to the invention, the positive electrode comprises at least one binder. The binder is a fluorinated binder, in particular polyvinylidene fluoride and / or a terpolymer formed by tetrafluoroethylene, hexafluoropropylene and vinylidene fluoride. However, it can also be a binder consisting of a polymer consisting of monomeric structural units of conjugated carboxylic acids or of alkali metal, alkaline earth metal or ammonium salts of conjugated carboxylic acids or a combination thereof. It is furthermore possible for the binder to consist of a polymer based on monomeric styrene and butadiene structural units. It can also be a binder consisting of a binder from the carboxymethylcellulose group. The binder is preferably present in the positive electrode in a concentration of at most 20% by weight, more preferably at most 15% by weight, more preferably at most 10% by weight, more preferably at most 7% by weight, more preferably at most 5% by weight and particularly preferably at most 2% by weight, based on the total weight of the positive electrode.
[0098] Rechargeable battery cell structure Advantageous developments of the rechargeable battery cell according to the invention are explained below with respect to its structure: In order to further improve the function of the rechargeable battery cell, in another advantageous development of the rechargeable battery cell according to the invention, the rechargeable battery cell has a number of negative electrodes and a number of positive electrodes arranged in a housing in an alternating stack. The positive and negative electrodes are preferably electrically separated from each other by a separator. However, the rechargeable battery cell can also be configured as a coil cell, in which the electrodes are configured as wound thin layers with a separator material. The separator, on the one hand, spatially and electrically separates the positive and negative electrodes, and on the other hand, is permeable, in particular to the ions of the active metal. This results in a large electrochemically effective surface, which allows a correspondingly high current yield.
[0099] The separator can be made of nonwovens, membranes, wovens, knits, organic materials, inorganic materials, or combinations thereof. Organic separators can be made of, for example, unsubstituted polyolefins (e.g., polypropylene or polyethylene), partially or fully halogen-substituted polyolefins (e.g., partially to fully fluorinated, in particular PVDF, ETFE, PTFE), polyesters, polyamides, or polysulfones. Separators comprising a combination of organic and inorganic materials are, for example, woven glass fiber materials, in which the glass fibers are provided with a suitable polymer coating. The coating is a fluorine-containing polymer, such as polytetrafluoroethylene (PTFE), ethylene tetrafluoroethylene (ETFE), perfluoroethylene propylene (FEP), THV (a terpolymer of tetrafluoroethylene, hexafluoroethylene, vinylidene fluoride), perfluoroalkoxy polymers (PFA), aminosilanes, polypropylene, or polyethylene (PE). The separator can also be provided folded in the housing of the rechargeable battery cell, for example in the so-called "Z-fold" configuration. In the case of Z-folding, the strip-shaped separator is folded in a Z shape so as to pass through the electrodes or around the electrodes. Furthermore, the separator may be formed as a separator paper.
[0100] It is within the scope of the present invention that the separator may be formed as a coating and that the high voltage electrode or the negative electrode are each covered by a coating. The coating can be formed using a nonwoven fabric, a membrane, a woven fabric, a knitted fabric, an organic material, an inorganic material, or a combination thereof.
[0101] The coating of the positive electrode ensures uniform ion migration and distribution in the rechargeable battery cell. The more uniform the ion distribution, especially in the negative electrode, the greater the possible loading of active material in the negative electrode and thus the usable capacity of the rechargeable battery cell. At the same time, the risk of non-uniform loading and the resulting precipitation of active metals is avoided. The advantages are particularly evident when the positive electrode of the rechargeable battery cell is covered by a coating.
[0102] The surface dimensions of the electrode and the coating are preferably coordinated with one another so that the outer dimensions of the coating on the electrode and the outer dimensions of the uncoated electrode match in at least one dimension.
[0103] The surface area of the coating may preferably be larger than the surface area of the electrode, in which case the coating extends beyond the boundaries of the electrode, so that two layers of the coating covering both sides of the electrode may be connected to each other by an edge connection at the edge of the positive electrode.
[0104] In a further preferred embodiment of the rechargeable battery cell according to the invention, the negative electrode has a coating whereas the positive electrode has no coating.
[0105] Further advantageous properties of the present invention are described and explained in detail below with the aid of figures, examples and experiments. [Brief description of the drawings]
[0106] [Figure 1] 1 is a cross-sectional view of a first example embodiment of a rechargeable battery cell according to the present invention; [Diagram 2] FIG. 2 is a detailed view of an electron microscope photograph of the three-dimensional pore structure of the metal foam according to the first embodiment of FIG. 1. [Diagram 3] FIG. 2 is a cross-sectional view of a second example embodiment of a rechargeable battery cell according to the present invention. [Figure 4] FIG. 4 is a diagram showing details of the second embodiment of FIG. 3. [Diagram 5] FIG. 11 is an exploded view of a third example embodiment of a rechargeable battery cell according to the present invention. [Figure 6] FIG. 11 is an exploded view of a third example embodiment of a rechargeable battery cell according to the present invention. [Figure 7] FIG. 1 shows the potential [V] as a function of capacity of an experimental cell having a three-electrode structure with hard carbon as the active electrode material during charging and discharging of the negative electrode. [Figure 8]FIG. 1 shows the potential [V] as a function of time of an experimental cell having a three-electrode configuration with metallic sodium as the active electrode material during multiple charging and discharging of the negative electrode. [Figure 9] FIG. 2 shows the potential course (in volts) as a function of capacity for cycle 1 and cycle 2 of an experimental cell having a three-electrode configuration with sodium cobaltate as the positive active material. [Figure 10] FIG. 1 shows the conductivity (unit [mS / cm]) of the electrolyte Na1 and the reference electrolyte as a function of the concentration of the conductive salt. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0107] FIG. 1 shows a cross-sectional view of a first embodiment of a rechargeable battery cell 2 according to the invention. The rechargeable battery cell 2 is formed as a prismatic cell and has, inter alia, a housing 1. The housing 1 encloses an electrode unit 3, which comprises three positive electrodes 4 and four negative electrodes 5. The positive electrodes 4 and the negative electrodes 5 are arranged in an alternating stack in the electrode unit 3. However, it is also possible for the housing 1 to accommodate more positive electrodes 4 and / or negative electrodes 5. In general, it is preferred that the number of negative electrodes 5 exceeds the number of positive electrodes 4 by one. Thereby, the outer end face of the electrode stack is formed by the electrode surface of the negative electrode 5. The electrodes 4, 5 are connected via electrode connections 6, 7 to corresponding connection contacts 9, 10 of the rechargeable battery cell 2. The rechargeable battery cell 2 is filled with an SO2-based electrolyte, which penetrates as completely as possible into all pores or cavities of the electrodes 4, 5, especially on the inside. The electrolyte is not shown in FIG. 1. In this embodiment, the positive electrode 4 comprises an intercalation compound as active material. The intercalation compound is NaCoO2.
[0108] In this embodiment, the electrodes 4, 5 are formed as planar layers, i.e. layers with a small thickness relative to the surface area of the electrodes. The electrodes are separated from each other by separators 11. The housing 1 of the rechargeable battery cell 2 is formed substantially cubic in shape, the electrodes 4, 5 and the walls of the housing 1, shown in cross-section, are formed substantially straight and flat, extending perpendicular to the drawing plane. The electrodes 4, 5 furthermore have conductor elements that are used to enable the necessary electronically conductive connection of the active materials of the respective electrodes. The conductor elements are in contact with the active materials (not shown in FIG. 1) participating in the electrode reactions of the respective electrodes 4, 5. The conductor elements are formed in the form of porous metal foams 18. The metal foams 18 extend over the thickness dimension of the electrodes 4, 5. The active materials of the positive and negative electrodes 4, 5 are respectively incorporated into the pores of the metal foams 18, so that the active materials uniformly fill the pores of the metal foam over the total thickness of the metal structure. To improve mechanical strength, the positive electrode 4 contains a binder. The binder is a fluoropolymer. The negative electrode 5 comprises as active material carbon in a form suitable for accepting sodium ions as an intercalation material. The structure of the negative electrode 5 is similar to that of the positive electrode 4.
[0109] Figure 2 illustrates an electron microscope photograph of the three-dimensional pore structure of the metal foam 18 of the first example embodiment in Figure 1. Based on the scale shown, it can be seen that the average diameter of the pores P is greater than 100 μm, i.e. relatively large. The metal foam is a metal foam made of nickel.
[0110] FIG. 3 shows a cross-sectional view of a second embodiment of a rechargeable battery cell 20 according to the invention. The second embodiment differs from the first embodiment shown in FIG. 1 in that the electrode unit comprises one positive electrode 23 and two negative electrodes 22. The electrodes are separated from each other by separators 21 and surrounded by a housing 28. The positive electrode 23 has a conductor element 26 in the form of a planar metal foil on which the active material 24 of the positive electrode 23 is applied on both sides. The negative electrode 22 likewise has a conductor element 27 in the form of a planar metal foil on which the active material 25 of the negative electrode 22 is applied on both sides. Alternatively, it is also possible to coat the active material on only one side of the planar conductor element of the edge electrode, i.e. the electrode that closes the electrode stack. The uncoated side faces the wall of the housing 28. The electrodes 22, 23 are connected via electrode connections 29, 30 to corresponding connection contacts 31, 32 of the rechargeable battery cell 20.
[0111] Figure 4 illustrates a planar metal foil used as the conductor elements 26, 27 of the positive and negative electrodes 23, 22, respectively, in the second example embodiment of Figure 3. The metal foil has a perforated or mesh-like structure with a thickness of 20 μm.
[0112] Fig. 5 shows an exploded view of a third embodiment of a rechargeable battery cell 40 according to the invention. The third embodiment differs from the previous two embodiments in that the positive electrode 44 is covered by a coating 13, the surface area of which is greater than that of the positive electrode 44, the boundary 14 of which is drawn in Fig. 5 by a dashed line. The two layers 15, 16 of the coating 13, which cover both sides of the positive electrode 44, are connected to each other by an edge connection 17 at the periphery of the positive electrode 44. The two negative electrodes 45 are uncoated. The electrodes 44 and 45 can be contacted via electrode connections 46 and 47.
[0113] FIG. 6 shows an exploded view of a third embodiment of a rechargeable battery cell 101 according to the invention. The important structural elements of the battery cell 101 are shown, with a wound electrode unit. The electrode unit 105 is formed by rolling a sheet-like starting material in a cylindrical housing 102 with a cover part 103. The sheet consists of several layers, including one positive electrode, one negative electrode and a separator extending between the electrodes, which electrically and mechanically isolates the electrodes from each other, but has sufficient porosity or ionic conductivity to allow the necessary ionic exchange. This creates a large electrochemically effective surface, which allows a correspondingly high current yield. The positive electrode has a conductor element in the form of a planar metal foil, on both sides of which a homogeneous mixture of the active material of the positive electrode is applied. The negative electrode also has a conductor element in the form of a planar metal foil, on both sides of which a homogeneous mixture of the active material of the negative electrode is applied.
[0114] The voids of the housing 102, unless occupied by the electrode unit 105, are filled with an electrolyte, not shown. The positive and negative poles of the electrode unit 105 are connected via corresponding terminal lugs 106 for the positive pole and 107 for the negative pole with terminal connections 108 for the positive pole and 109 for the negative pole, thereby allowing the electrical connection of the rechargeable battery cell 101. As an alternative to the electrical connection of the negative pole via the terminal lugs 107 and the terminal connection 109, as shown in FIG. 6, the electrical connection of the negative pole can also be made via the housing 102. EXAMPLES
[0115] Example 1 Preparation of reference electrolyte For the experiments described below, a SO2-based reference electrolyte was prepared. For this purpose, the conductive salt Li1 was prepared according to the method described in the following literature [V5]: [V5] I. Krossing, European Journal of Chemistry, 2001, 7, 490
[0116] Compound 1 is a family of polyfluoroalkoxyaluminates, which can be synthesized by the reaction of LiAlH4 with the corresponding alcohol R-OH(R 1 =R 2 =R 3 =R 4 ) and prepared according to the following reaction scheme: [ka]
[0117] This formed compound Li1, having the molecular or structural formula shown below: [ka]
[0118] To prepare the reference electrolyte, the compound Li1 was dissolved in SO2. The concentration of the conductive salt in the reference electrolyte was 0.6 mol / L.
[0119] Example 2: Preparation of Example Embodiments of SO2-Based Electrolytes for Battery Cells For the experiments described below, an embodiment of an SO2-based electrolyte was prepared. For this purpose, the compound Na1 shown below as a conductive salt according to formula (I) was prepared according to the preparation method described in the following document [V6]: [V6] P. J. Malinowski et al., Dalton Transactions, 2020, 49, 7766-7773 Conductive salts according to formula (I) can be prepared by reacting NaAlH4 with the corresponding alcohol R-OH(R 1 =R 2 =R 3 =R 4 ) and prepared according to the following reaction scheme: [ka]
[0120] This formed compound Na1, having the molecular or structural formula shown below: [ka]
[0121] Compound Na1 was then dissolved in SO2 at low temperature or under pressure according to method steps 1 to 4 described below: 1) Place each compound Na1 in a pressure flask equipped with a riser pipe (Steigrohr), 2) evacuating the pressure flask; 3) Liquid SO2 is injected, and 4) Repeat steps 2 and 3 until the target amount of SO2 has been added.
[0122] Thus, electrolyte Na1 was obtained. The concentration of compound Na1 in the electrolyte was 0.6 mol / l (substance amount concentration per 1 liter of electrolyte) unless otherwise specified in the following experimental description. The following experiments were carried out using electrolyte Na1 and a reference electrolyte.
[0123] Experiment 1: Behavior of a negative electrode made of hard carbon The experiments were carried out in an experimental cell with a three-electrode structure (working electrode, counter electrode, and reference electrode), where the counter electrode and the reference electrode were metallic sodium. The working electrode was an electrode with an active material made of hard carbon (English: hard carbon). The composition of the electrode was 96% by weight of hard carbon (English: hard carbon) and 4% by weight of binders CMC and SBR in total. The conductor element was a foil made of aluminum. The half-cell was filled with the electrolyte Na1.
[0124] The half-cell was charged multiple times to a potential of 0.005 V and discharged to a potential of 1.5 V at a charge / discharge rate of 0.1 C. Figure 7 illustrates the potentials of the charge and discharge curves of the half-cell during the fifth cycle. The dashed and dotted lines correspond to the potentials of the charge curve and the solid lines correspond to the potentials of the discharge curve.
[0125] The charge / discharge curves show typical battery behavior with good cycling efficiencies of over 95%.
[0126] Experiment 2: Behavior of metallic sodium anode The experiments were carried out in an experimental cell with a three-electrode configuration (working electrode, counter electrode and reference electrode), where the counter electrode and the reference electrode were metallic sodium. The working electrode was an aluminum foil. The half-cell was filled with the electrolyte Na1.
[0127] Deposition (charging) and dissolution (discharging) of metallic sodium were carried out. For this purpose, we started with a 0.25 mAh / cm 2 After that, the battery was discharged to a potential of 0.5 V. The charge and discharge rates were 0.1 mA / cm 2 Figure 8 shows the potential course of five charge-discharge cycles versus time.
[0128] The deposition and dissolution of metallic sodium shows a uniform course over the five cycles.
[0129] Experiment 3 Composition Na as active electrode material 0.7 Chief of Staff 2 Experimental cell with sodium cobaltate having To investigate sodium cobaltate as the active electrode material at the positive electrode in the electrolyte Na1, an experimental cell with a three-electrode configuration (working electrode, counter electrode, and reference electrode) was fabricated. The active material at the positive electrode (cathode) was of the composition Na 0.7 The total positive electrode composition was sodium cobaltate with CoO2. 0.7 The electrolyte was 94% CoO2, 4% PVDF binder, and 2% carbon black. The conductor element was aluminum foil. The counter and reference electrodes consisted of metallic sodium. The experimental cell was filled with the electrolyte Na1.
[0130] The experimental cell was charged to an upper potential of 4.2 V at a charge rate of 0.1 C. It was then discharged to a discharge potential of 2.0 V at a discharge rate of 0.1 C. Figure 9 shows the potential course (in [V]) for the first two charge-discharge cycles as a function of charge (in %) at maximum charge.
[0131] The potential curves show a stable charge / discharge behavior, the curve progression being typical for this type of electrode material.
[0132] Experiment 4: Measurement of the conductivity of the electrolyte Na1 in comparison with a reference electrode For the conductivity measurements, Na1 electrolytes were prepared with different concentrations of compound Na1. For each concentration of compound, the conductivity of the electrolyte was measured using a conductometric method, in which a four-electrode sensor was held in contact with the solution after tempering, with a measurement range of 0.02 to 500 mS / cm.
[0133] Similar measurements were performed using a reference electrolyte.
[0134] Figure 10 illustrates the conductivity of the electrolyte Na1 versus the concentration of compound Na1. For comparison, the conductivity of the reference electrolyte is plotted versus the concentration of the corresponding Li compound (see [V4]). A maximum conductivity is found with a high conductivity value of about 48 mS / cm when the concentration of compound Na1 is 0.6 mol / L. In contrast, the reference electrolyte has a maximum conductivity of about 38 mS / cm when the concentration of compound Li1 is between 0.6 mol / L and 0.7 mol / L.
[0135] Thus, the electrolyte Na1 with the conductive salt Na1 has a better conductivity than the reference electrolyte with the corresponding lithium compound Li1. This is very surprising because, on the one hand, as mentioned above, lithium compounds showed better conductivity than sodium compounds in prior art SO2-based electrolytes (see [V1] US 4,891,281). On the other hand, a better conductivity would be expected also for lithium electrolytes, since sodium ions are larger than lithium ions. The experimental results summarized in Table 1 show some surprising results regarding the conductivity.
[0136] [Table 1] In contrast, organic electrolytes known from the prior art, such as LP30 (1M LiPF6 / EC-DMC (1:1 by weight), have a conductivity of only about 10 mS / cm.
Claims
1. A rechargeable battery cell (2, 20, 40, 101) comprising an active metal, at least one positive electrode (4, 23, 44), at least one negative electrode (5, 22, 45), a housing (1, 28, 102), and an electrolyte, the active metal is sodium; The electrolyte is SO 2 It is a system, I 【Chemistry 1】 comprising at least a first conductive salt having the formula (I): - Substituent R 1 , R 2 , and R 3 are independently halogen atoms, hydroxy groups and chemical groups -OR 5 and the substituent R 4 is a hydroxy group and a chemical group -OR 5 is selected from the group formed by - Substituent R 5 is C 1 ~C 10 Alkyl, C 2 ~C 10 Alkenyl, C 2 ~C 10 Alkynyl, C 3 ~C 10 Cycloalkyl, C 6 ~C 14 Aryl, and C 5 ~C 14 heteroaryl, wherein the aliphatic, cyclic, aromatic, and heteroaromatic groups may be unsubstituted or substituted; Z is aluminum or boron, and - Substituent R 1 , R 2 , R 3 , and R 4 at least two of said ligands are capable of forming a chelating ligand coordinated to Z.
2. The active metal is - sodium metal, and / or at least one sodium storage material selected from the group formed by intercalation materials, adsorption materials, alloy-forming materials and conversion materials; 2. The rechargeable battery cell (2, 20, 40, 101) according to claim 1, characterized in that:
3. 3. The rechargeable battery cell (2, 20, 40, 101) according to claim 2, characterized in that the sodium storage material is a carbon-containing intercalation material selected from the group formed by hard carbon, soft carbon, graphene, and heteroatom-doped carbon.
4. The sodium storage material is a carbon-free intercalation material, preferably sodium titanate, in particular Na 2 Ti 3 O 7 or NaTi 2 (P.O. 4 ) 3 3. The rechargeable battery cell (2, 20, 40, 101) according to claim 2, characterized in that:
5. The sodium storage material is - sodium-storing metals and metal alloys, preferably Sn, Sb, or - sulfides and oxides of said sodium-storing metals and metal alloys, preferably SnS x , SbS x , or Sn, Sb oxide glass 3. The rechargeable battery cell (2, 20, 40, 101) according to claim 2, characterized in that the sodium alloy-forming material is selected from the group formed by:
6. The sodium storage material is selected from the group consisting of sulfides, oxides, selenides and fluorides of the metals Ti, V, Cr, Mn, Fe, Co, Ni, Cu and Zn, preferably iron sulfide (FeS x ), iron selenide (FeSe x ), iron fluoride (FeF x ), iron oxide (FeO x ), cobalt oxide (CoO x ), nickel oxide (NiO x ), and copper oxide (CuO x 3. The rechargeable battery cell (2, 20, 40, 101) according to claim 2, characterized in that the conversion material is selected from the group formed by:
7. 3. The rechargeable battery cell (2, 20, 40, 101) of claim 2, characterized in that the negative electrode (5, 22, 45) comprises a combination of at least one sodium-alloying anode material and at least one carbon-containing intercalation material.
8. The positive electrode (4, 23, 44) preferably contains Na x M' y M” z O a Contains at least one compound having a composition M' is at least one metal selected from the group formed by the elements Ti, V, Cr, Mn, Fe, Co, Ni, Cu and Zn, M″ is at least one element selected from the group formed by the elements of groups 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 and 16 of the Periodic Table of the Elements, x and y are each independently a number greater than 0; z is a number equal to or greater than 0, and - a is a number greater than 0 A rechargeable battery cell (2, 20, 40, 101) according to any one of the preceding claims.
9. 9. A rechargeable battery cell (2, 20, 40, 101) according to any one of claims 1 to 8, characterized in that the positive electrode (4, 23, 44) is chargeable to an upper potential of at least 3.6 volts, preferably to a potential of at least 3.8 volts, more preferably to a potential of at least 4.0 volts, even more preferably to a potential of at least 4.2 volts and particularly preferably to a potential of at least 4.4 volts.
10. The substituent R of the first conductive salt 1 , R 2 , R 3 , and R 4 are each independently a chemical group -OR 5 R 5 is C 1 ~C 10 Alkyl, C 2 ~C 10 Alkenyl, C 2 ~C 10 Alkynyl, C 3 ~C 10 Cycloalkyl, C 6 ~C 14 Aryl and C 5 ~C 14 10. The rechargeable battery cell (2, 20, 40, 101) according to any one of claims 1 to 9, characterized in that the aryl group is selected from the group formed by aliphatic, cyclic, aromatic and heteroaromatic groups, which may be unsubstituted or substituted.
11. The R 5 teeth, - C 1 ~C 6 Alkyl, preferably C 2 ~C 4 Alkyl, particularly preferably 2-propyl, methyl and ethyl, - C 2 ~C 6 Alkenyl, preferably C 2 ~C 4 alkenyl, particularly preferably ethenyl and propenyl; - C 2 ~C 6 Alkynyl, preferably C 2 ~C 4 Alkynyl, - C 3 ~C 6 Cycloalkyl, - Phenyl, and - C 5 ~C 7 Heteroaryl, aliphatic, cyclic, aromatic and heteroaromatic groups may be unsubstituted or substituted; 10. A rechargeable battery cell (2, 20, 40, 101) according to any one of claims 1 to 9, characterized in that it is selected from the group formed by:
12. The substituent R 5 The aliphatic, cyclic, aromatic and heteroaromatic groups are one or more halogen atoms, in particular fluorine atoms, or - C 1 ~C 4 Alkyl, C 2 ~C 4 Alkenyl, C 2 ~C 4 Alkynyl, phenyl, benzyl, and fully or partially halogenated, especially fully or partially fluorinated, C 1 ~C 4 Alkyl, C 2 ~C 4 Alkenyl, C 2 ~C 4 A chemical group selected from the group consisting of alkynyl, phenyl, and benzyl.
12. A rechargeable battery cell (2, 20, 40, 101) according to any one of claims 1 to 11, characterized in that it can be further replaced by
13. The substituent R 5 At least one CF 3 Group, or OSO 2 CF 3 13. A rechargeable battery cell (2, 20, 40, 101) according to any one of claims 10 to 12, characterized in that it is substituted with a group.
14. The chelating ligands are in particular of the formula -O-R 5 14. A rechargeable battery cell (2, 20, 40, 101) according to any one of claims 1 to 13, characterized in that it is formed so as to be bidentate or polydentate based on -O.
15. 15. A rechargeable battery cell (2, 20, 40, 101) according to any one of claims 1 to 14, characterized in that the first conductive salt is selected from the group formed by: 【Chemistry 2】
16. The electrolyte is, based on the total weight of the electrolyte composition, (i) from 5 to 99.4% by weight of sulfur dioxide; (ii) 0.6 to 95 wt. % of the first conductive salt; (iii) 0 to 25 weight percent of a second conductive salt, and (iv) 0 to 10% by weight of additives 16. A rechargeable battery cell (2, 20, 40, 101) according to any one of claims 1 to 15, characterized in that it has the composition
17. 17. A rechargeable battery cell (2, 20, 40, 101) according to any one of claims 1 to 16, characterized in that the concentration of the substance of the first conductive salt is in the range of 0.01 mol / L to 10 mol / L, preferably 0.05 mol / L to 10 mol / L, more preferably 0.1 mol / L to 6 mol / L, and particularly preferably 0.2 mol / L to 3.5 mol / L relative to the total volume of the electrolyte.
18. The electrolyte contains at least 0.1 mole of SO per mole of conductive salt. 2 , preferably at least 1 mole of SO 2 , more preferably at least 5 moles SO 2 , more preferably at least 10 moles of SO 2 and particularly preferably at least 20 moles of SO 2 18. A rechargeable battery cell (2, 20, 40, 101) according to any one of claims 1 to 17, characterized in that it comprises
19. 19. A rechargeable battery cell (2, 20, 40, 101) according to any one of claims 1 to 18, characterized in that the total amount of organic solvents in the electrolyte is at most 50% by weight, preferably at most 40% by weight, further preferably at most 30% by weight, further preferably at most 20% by weight, further preferably at most 15% by weight, further preferably at most 10% by weight, further preferably at most 5% by weight or further preferably at most 1% by weight, particularly preferably the electrolyte is free of organic solvents.
20. 20. The rechargeable battery cell (2, 20, 40, 101) according to any one of the preceding claims, characterized in that the conductor element of the negative electrode (5, 22, 45) is made from nickel, copper or aluminium.
Citation Information
Patent Citations
Rechargeable battery cell
WO2021019043A1
Sodium-sulfur dioxide secondary battery and method of manufacturing the same
EP2860799A1
Sodium-metal chloride secondary battery and method of manufacturing the same
EP2860811A1
So2-based electrolyte for rechargeable battery cell and rechargeable battery cell comprising the same
EP3772129A1
Electrochemical cells having low vapor pressure complexed SO2 electrolytes
US4891281A